Genetic load determines atrophy in hand cortico‐striatal pathways in presymptomatic Huntington's disease. Issue 10 (24th May 2018) - Hong, Yi; O'Donnell, Lauren J.; Savadjiev, Peter; Zhang, Fan; Wassermann, Demian; Pasternak, Ofer; Johnson, Hans; Paulsen, Jane; Vonsattel, Jean‐Paul; Makris, Nikos; Westin, Carl F.; Rathi, Yogesh
Abstract: Huntington's disease (HD) is an inherited neurodegenerative disorder that causes progressive breakdown of striatal neurons. Standard white matter integrity measures like fractional anisotropy and mean diffusivity derived from diffusion tensor imaging were analyzed in prodromal‐HD subjects; however, they studied either a whole brain or specific subcortical white matter structures with connections to cortical motor areas. In this work, we propose a novel analysis of a longitudinal cohort of 243 prodromal‐HD individuals and 88 healthy controls who underwent two or more diffusion MRI scans as part of the PREDICT‐HD study. We separately trace specific white matter fiber tracts connecting the striatum (caudate and putamen) with four cortical regions corresponding to the hand, face, trunk, and leg motor areas. A multi‐tensor tractography algorithm with an isotropic volume fraction compartment allows estimating diffusion of fast‐moving extra‐cellular water in regions containing crossing fibers and provides quantification of a microstructural property related to tissue atrophy. The tissue atrophy rate is separately analyzed in eight cortico‐striatal pathways as a function of CAG‐repeats (genetic load) by statistically regressing out age effect from our cohort. The results demonstrate a statistically significant increase in isotropic volume fraction (atrophy) bilaterally in hand fiber connections to the putamen with increasing CAG‐repeats, which connects the genetic abnormality (CAG‐repeats) to an imaging‐based microstructural marker of tissue integrity in specific white matter pathways in HD. Isotropic volume fraction measures in eight cortico‐striatal pathways are also correlated significantly with total motor scores and diagnostic confidence levels, providing evidence of their relevance to HD clinical presentation.